OBSTACLES FACED BY PRE-SERVICE ENGLISH TEACHERS DURING TEACHERS PROFESSIONAL EDUCATION PROGRAM (PPG) - Mawaddah Warahmah; Afrianto Daud; Novitri Novitri (International Journal of Educational Best Practices, 2021)
The government in Indonesia issues new rules to prepare pre-service teachers to be professional teachers in the future by asking them to attend additional education named Teachers Professional Education Program (locally known as Program Profesi Guru).  This Case Study aimed to identify the obstacles experienced by pre-service English teachers in FKIP Universitas Riau during the PPG program and the Teaching Practicum (PPL) as a part of PPG program. This is qualitative research involving 10 alumni of the Subsidized PPG English Education Department. Focus Group Discussion was used to collect data from the participants. The data obtained were analyzed using Miles and Huberman’s thematic analysis and referred to the three procedures introduced by Flick i.e., open coding, axial coding and selective coding with the help of the Nvivo 12 software. The findings showed seven emerging obstacles faced by the pre-service English teachers during Teachers Professional Education Program (PPG). There were one (1) obstacle found at the first-semester theory program in PPG, and six (6) obstacles found at the second-semester practicum program in PPG which known as PPL.